2007
DOI: 10.1007/bf03175351
|View full text |Cite
|
Sign up to set email alerts
|

Nuclease-producing bacteria in soil cultivated with herbicide resistant transgenic white poplars

Abstract: This study was carried out using soil cultivated, under greenhouse conditions, with transgenic white poplars expressing the bar gene for tolerance to the Basta ® herbicide. The occurrence of extracellular nucleolytic activity was monitored in soil samples collected at four different times over a 26-month period. The fraction of nuclease producing bacteria (NPB) ranged from 62.5 to 100% of the total culturable bacterial population. The DNA-methyl green plate assay allowed to distinguish five groups of bacteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…When the root tip is treated with DNase, this NET-like mantle is destroyed and the normal resistance to infection is abolished. Like human pathogens that produce extracellular DNase activities now known to be involved in virulence (Sherry and Goeller, 1950;Sumby et al, 2005;Buchanan et al, 2006), rootassociated bacteria and fungi also produce extracellular DNase activities (Klosterman et al, 2001;Tavares and Sellstedt, 2001;Balestrazzi et al, 2007). Klosterman et al (2001) have proposed that such enzymes in pathogenic fungi function by entering the nuclei of plant cells and causing DNA damage that triggers defense responses in nonhost tissues.…”
Section: Discussionmentioning
confidence: 99%
“…When the root tip is treated with DNase, this NET-like mantle is destroyed and the normal resistance to infection is abolished. Like human pathogens that produce extracellular DNase activities now known to be involved in virulence (Sherry and Goeller, 1950;Sumby et al, 2005;Buchanan et al, 2006), rootassociated bacteria and fungi also produce extracellular DNase activities (Klosterman et al, 2001;Tavares and Sellstedt, 2001;Balestrazzi et al, 2007). Klosterman et al (2001) have proposed that such enzymes in pathogenic fungi function by entering the nuclei of plant cells and causing DNA damage that triggers defense responses in nonhost tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Some bacteria and fungi closely associated with plant roots have been reported to exhibit exDNase activities (Greaves and Webley 1965;Bertagnolli et al 1996;Tavares and Sellstedt 2001;Klosterman et al 2001;Balestrazzi et al 2007). It was thought that only a limited number of bacterial species produce nucleases extracellularly (Benedik and Strych 1998); however, studies have found that many bacterial species exude nucleases that are either anchored to the cell wall or exuded into the growth medium (Eaves and Jeffries 1963;Nakai et al 1965;Rothberg and Swartz 1965;Greaves and Webley 1965;Jakubovics et al 2013;Sheikh and Hosseini 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Greaves and Wilson (1970) also recorded large numbers of DPB from different soil types growing grassy vegetation with varying proportions of DPBs at 17% in kaolinite, 86% in montmorillonite, 58% in peat and 47% in sandy soils. In an indoor study carried out by Balestrazzi et al (2007) using transgenic white poplars with the bar gene insert, 62.5 to 100% of the total culturable bacterial populations were observed to express exDNase activities. Moreover, bacterial isolates cultured and identified as DNase producers in their study belonged to five genera: Bacillus, Brevibacillus, Microbacterium, Pseudomonas and Stenotrophomonas.…”
Section: Introductionmentioning
confidence: 99%
“…Aim of this study was to develop an improved protocol for DNA extraction and purification from a humic acid-rich soil used to establish two extensive greenhouse trials with transgenic white poplars (Balestrazzi et al, 2007(Balestrazzi et al, , 2008(Balestrazzi et al, , 2009a(Balestrazzi et al, , 2009bBonadei et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This soil has been used for the cultivation of transgenic white poplars engineered with the StSy gene from Vitis vinifera and with the bar gene from Streptomyces hygroscopicus, respectively, in greenhouse trials (Balestrazzi et al, 2007(Balestrazzi et al, , 2008(Balestrazzi et al, , 2009a(Balestrazzi et al, , 2009bBonadei et al, 2009). In the GM poplars expressing the StSy gene encoding stilbene synthase, responsible for resveratrol biosynthesis, the amount of resveratrol-like compounds was in the range 180-210 mg kg -1 fresh leaf tissue (Balestrazzi et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%